Indicadores para medir la adquisición de competencias en las primeras experiencias profesionales en ingeniería - Velia Artigas, María (2025)
This article examines the extent to which advanced engineering students and recent graduates from the Universidad Nacional de Mar del Plata (Argentina) perceive they have acquired key competencies during their initial professional experiences. To address the limited understanding of whether their academic training aligns with labor market expectations, the study employs two indicators—the Competence Adequacy Indicator (IAC) and the Competence Development Indicator (IDC)—to evaluate the relationship between what students learned, what they expected to learn, and what was required in the workplace. Using an exploratory and descriptive approach, the research surveyed 53 individuals through self-administered questionnaires assessing generic, technological, and social competencies. The findings reveal high expectations regarding competency training and varying gaps between perceived acquisition and workplace demands, with notable differences between Industrial Engineering students and the broader engineering cohort. The study concludes that these indicators offer a valuable reference for monitoring the effectiveness of the faculty’s new competency-based curricula.